Fundamentals of prosthetic urology - Akula, Kole P (Asian J Androl, 2019)
The field of prosthetic urology demonstrates the striking impact that simple devices can have on quality of life. Penile prosthesis and artificial urinary sphincter implantation are the cornerstone procedures on which this specialty focuses. Modern research largely concentrates on decreasing the rates of complication and infection, as the current devices offer superior rates of satisfaction when revision is not necessary. These techniques are also able to salvage sexual function and continence in more difficult patient populations including female-to-male transgender individuals, those with ischemic priapism, and those with erectile dysfunction and incontinence secondary to prostatectomy. This review summarizes modern techniques, outcomes, and complications in the field of prosthetic urology.